Modulation of Macrophages by In Situ Ligand Bridging. (8th February 2023) - Kim, Seong Yeol; Thangam, Ramar; Kang, Nayeon; Hong, Hyunsik; Kim, Chowon; Lee, Sungkyu; Son, Subin; Lee, Hyun‐Jeong; Tag, Kyong‐Ryol; Min, Sunhong; Jeong, Daun; Hwang, Jangsun; et al.
Abstract: Extracellular matrix (ECM) proteins containing cell‐attachable Arg‐Gly‐Asp (RGD) sequences exhibit variable bridging and non‐bridging in fibronectin‐collagen and laminin‐collagen complexes that can regulate inflammation, tissue repair, and wound healing. In this study, linking molecule‐mediated conjugation of 1D magnetic nanocylinders (MNCs) to material surfaces pre‐decorated with gold nanospheres (GNSs) is performed, thereby yielding RGD‐coated MNCs (RGD‐MNCs) over RGD‐coated GNSs (RGD‐GNSs) in a non‐bridging state. The RGD‐MNCs are drawn closer to the RGD‐GNSs via magnetic field‐mediated compression of the linking molecules to establish the bridging between them. Relative proportion of the RGD‐MNCs to the RGD‐GNSs is optimized to yield effective remote stimulation of integrin binding to variably bridged RGDs similar to that of invariably bridged RGDs used as a control group. Remote manipulation of the RGD bridging facilitates the attachment structure assembly of macrophages that leads to pro‐healing/anti‐inflammatory phenotype acquisition. In contrast, the non‐bridged RGDs inhibited macrophage attachment that acquired pro‐inflammatory phenotypes. The use of various nanomaterials in constructing heterogeneous RGD‐coated materials can further offer various modes in remote switching of RGD bridging and non‐bridging to understand dynamic integrin‐mediated modulation of macrophages that regulate immunomodulatory responses, such as foreign body responses, tissue repair, and wound healing. Abstract : RGD‐coated materials of 1D magnetic RGDs over non‐magnetic RGDs are developed to enable remote manipulation of variable RGD bridging. Remote control of RGD bridging and non‐bridging reversibly regulates integrin binding and adhesion structure assembly that modulate the functional polarizations for pro‐inflammatory or pro‐healing immunoregulation of host macrophages.